Diseño de un biodigestor de gas producido por el estiércol de los cerdos en la vereda juracambita del municipio de Zetaquira (2023)
This degree work was based on the need to apply a process management through intervals of organic waste generated by pigs in the agricultural facilities of the Juracambita village, municipality of Zetaquira. The objective of this work is to show how a biodigester was designed to process pig manure waste and thus take advantage of it for reuse and treatment, filtering it chemically, physically and biologically, constituting a source of renewable energy.